Determination of Calcium and Magnesium Levels in PAMSIMAS Clean Water, Sangginora, Poso - Alfian Tuba; Tahril Tahril; Paulus H. Abram; sri H. V Pulukadang (Jurnal Akademika Kimia, 2026)
Clean water is one of the most essential needs in human life, so we need to ensure it is available in adequate quantity and quality. In addition to being consumed, clean water can be used to improve welfare by enhancing health. The availability of clean water in people's lives is very important. It needs to be considered because water contains many minerals, which should be known in terms of standard quality levels. The purpose of this study was to determine the levels of calcium and magnesium and to assess the physical and chemical properties of PAMSIMAS water in Sangginora Village, Poso Pesisir Selatan District. Mineral levels were determined by the Atomic Absorption Spectrophotometry (AAS) analysis method. The results of the study obtained from PAMSIMAS Water samples taken from the water tank (main tank) were the calcium mineral content of 14.89 mg/L, residents' water taps 18.957 mg/L and magnesium (Mg) mineral content in the water tank (main tank) 1.57 mg/L, residents' water taps 2.191 mg/L. The levels of calcium and magnesium minerals in water increase from the sampling point in the main tank to the residents' taps. This is due to the lack of government attention to the cleanliness of the flowing water pipes. Based on the results, the calcium mineral content in clean water is not suitable for consumption, whereas the magnesium mineral content is still suitable for consumption according to the clean water quality standard set by PERMENKES.